ANALISIS FATWA DSN-MUI NOMOR 143/DSN-MUI/VIII/2021 TENTANG PEMBIAYAAN PERSONAL (AT-TAMWIL ASY-SYAKHSHI/PERSONAL FINANCING) - Adhiningdyah Mulyani Taufiqs; Mahmud; Sabrina Nur Baiti; Muh. Nashirudin (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
This literature-based study assesses the legal design, practical effects, and limiting factors concerning the enactment of DSN-MUI Regulation No. 143/2021 on Individual Funding (at-Tamwil Asy-Syakhshi) within the Indonesian Sharia finance landscape. The Regulation is a vital legal directive that validates the provision of quick private funds via the social Qardh contract or sales arrangements (Murabahah, etc.), while simultaneously maintaining religious adherence by prohibiting behaviors leading to ethical hazards. Findings point to a significant gap in practice; the commercial agreement Murabahah predominates (reaching 44%), considerably surpassing Qardh. This is driven by institutional profit motives, LKS's view of Qardh as high-risk, and prudential compliance rules. Murabahah faces issues related to ownership rights violation, whereas Qardh suffers from limited internal funds and insufficient state fiscal backing to absorb social liabilities, contrasting sharply with globally successful state-backed models like Saudi Arabia's Social Development Bank. Effective adoption necessitates robust institutional cooperation: LKS must transition Qardh risk oversight to a communal foundation, and BMTs are advised to implement a Compulsory Cross-Subsidy Framework to finance Qardh independently, establishing it as a rapid, ethical alternative to usurious lenders.